1990
DOI: 10.1002/hep.1840120404
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of hepatic lymphokine-activated killer cell induction by murine kupffer cells and hepatocytes

Abstract: Murine lymphokine-activated-killer cell activity was readily induced by culturing spleen cells with 10 U/ml of interleukin-2 for 4 days. In contrast, very little activity was generated under the same culture conditions when nonparenchymal liver cells were used as the responding cells. It was concluded that Kupffer cells produced prostaglandin and interferon alpha/beta, which suppressed lymphokine-activated-killer induction because (a) induction of lymphokine-activated-killer activity from nonparenchymal liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
1

Year Published

1990
1990
1995
1995

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
3
13
1
Order By: Relevance
“…The activities examined were those of allogeneic CTL, LAK, phagocytic macrophage (Fc-dependent) and tumoricidal macrophage. Several of these activities have been shown previously to be modified by PGE2 and/or indomethacin [2,3,22,24,35,40] …”
Section: Effect Of In Vitro Indomethacin On Host De¢ènse Functions Ofmentioning
confidence: 43%
“…The activities examined were those of allogeneic CTL, LAK, phagocytic macrophage (Fc-dependent) and tumoricidal macrophage. Several of these activities have been shown previously to be modified by PGE2 and/or indomethacin [2,3,22,24,35,40] …”
Section: Effect Of In Vitro Indomethacin On Host De¢ènse Functions Ofmentioning
confidence: 43%
“…It was demonstrated that rat hepatocytes suppress the natural cytotoxicity of nonparenchymal liver cells (NPCs) against YAC-1 lymphoma and P815 plasmacytoma cells (17). More recently, we reported that murine hepatic lymphokine-activated-killer cell generation in uitro was markedly inhibited by hepatocytes and liver cytosolic extract (LEx), which appeared to suppress the early phase of interleukin (IL) 2-induced lymphocyte transformation (18). Furthermore, supplementation of the culture medium with up to 5 mmol/L arginine could only partially reverse the inhibitory activity of LEx.…”
supporting
confidence: 40%
“…Independently, Chisari et al (11) identified two hepatic immunoregulatory molecules from rat liver perfusate, L-arginase released by injured hepatocytes and very-lowdensity lipoprotein (VLDL) secreted by intact hepatocytes. Several less-well-characterized factors have also been shown to possess imrnunoinhibitory activityWe have studied the role of parenchymal liver cells (hepatocytes) on hepatic immune responses (17,18). It was demonstrated that rat hepatocytes suppress the natural cytotoxicity of nonparenchymal liver cells (NPCs) against YAC-1 lymphoma and P815 plasmacytoma cells (17).…”
supporting
confidence: 39%
“…As previously reported by us [24,27], murine Kupffer cells, when placed in tissue-culture medium in the absence of such stimulators as LPS and IFN 7, produced substantial amounts of IFN~B, which was not detected with splenic macrophages, perito-neal macrophages and blood monocytes under the same experimental conditions. We have further shown that induction of lymphokine-activated-killer (LAK) activity from nonparenchymal liver cells (NPC) was suppressed by this endogenous IFN~/[3 produced specifically by Kupffer cells [27].…”
Section: Lntroductionmentioning
confidence: 44%
“…Past observations by us [1,24,27] and other investigators [4,11,26] have demonstrated the differences in both functional and biochemical characteristics between several macrophage populations including liver macrophages (Kupffer cells), peritoneal macrophages, splenic macrophages, alveolar macrophages and blood monocytes. For instance, Kupffer cells, which play a major role in clearing gut-derived antigens and microbial products, have been shown to display several times more phagocytic activity than peritoneal macrophages [11].…”
Section: Lntroductionmentioning
confidence: 45%